2018
DOI: 10.1016/j.cognition.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Abstraction promotes creative problem-solving in rhesus monkeys

Abstract: Abstraction allows us to discern regularities beyond the specific instances we encounter. It also promotes creative problem-solving by enabling us to consider unconventional problem solutions. However, the mechanisms by which this occurs are not well understood. Because it is often difficult to isolate human high-level cognitive processes, we utilized a nonhuman primate model, in which rhesus monkeys appear to use similar processes to consider an unconventional solution to the difficult reverse-reward problem:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…Future studies on abstraction should be planned to test whether the task variables encoded in an abstract form, as opposed to those that are not, would facilitate the generalization of the rules to new items or conditions. The ability of generalization has been reported by several studies on macaques [37, 38, 39, 35]. For example, Falcone et al [39] have shown that monkeys can transfer the nonmatch-to-goal rule from the object domain to the spatial domain in a single session, and Sampson et el.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Future studies on abstraction should be planned to test whether the task variables encoded in an abstract form, as opposed to those that are not, would facilitate the generalization of the rules to new items or conditions. The ability of generalization has been reported by several studies on macaques [37, 38, 39, 35]. For example, Falcone et al [39] have shown that monkeys can transfer the nonmatch-to-goal rule from the object domain to the spatial domain in a single session, and Sampson et el.…”
Section: Discussionmentioning
confidence: 94%
“…The ability of generalization has been reported by several studies on macaques [46, 47, 48, 44]. For example, Falcone et al [48] have shown that monkeys can transfer the nonmatch-to-goal rule from the object domain to the spatial domain in a single session, and Sampson et el.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations